Pemanfaatan SIG Dalam Pemetaan Bidang Tanah Di Kantor ATR/BPN Kabupaten Kolaka - Wahyuddin; Utomo, Pradityo; Dede Sopiandy (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
This study discusses the utilization of Geographic Information Systems (GIS) for land parcel mapping at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) in Kolaka Regency. The implementation of GIS through the Land Activity Computerization Program (KKP) aims to enhance efficiency and accuracy in land registration processes while providing legal certainty over land ownership. By integrating spatial and textual data, GIS can deliver comprehensive information, enabling faster and more structured land mapping. Data obtained from the KKP at the Kolaka Land Office shows a significant increase in the number of registered land parcels after implementing GIS. Prior to GIS adoption, land registration data was limited and fragmented, with spatial data that lacked accuracy and accessibility. Post-implementation of KKP, the number of registered land parcels increased by 85% over the last 10 years, reflecting the system's improved effectiveness in supporting land administration. The results indicate that GIS can accelerate the mapping process, improve data accessibility, and facilitate spatial planning. With thematic maps generated, the ATR/BPN can conduct better analyses of land quality and legal status. Additionally, GIS helps identify areas requiring data updates, thereby continuously enhancing the quality and accuracy of land information. This study concludes that GIS is not only a mapping tool but also a strategic solution that increases efficiency and transparency in land management. These findings provide a potential model for other regions aiming to optimize land registration through GIS-based technology, supporting legal security and certainty for the public.